"What is the best language for Eastern Europe?" Lingua receptiva as a new approach in Slavic intercommunication research - Steciąg, Magdalena (Slavia Centralis, 2020)
The aim of the paper is to consider the notion of lingua receptiva as a new approach in Slavic intercommunication studies which allows to analyze interlingual contacts from a different perspective, going beyond the traditional structuralist or glottodidactic approaches. So far, most research on lingua receptiva has been conducted in relation to Scandinavian and Romance languages. There are, however, examples of initial research done on Slavic languages. This paper will present an overview of the main results of these studies, along with concepts developed in them.
Keywords: lingua receptiva; inclusive multilingualism; Slavic languages; Eastern Europe